Transformation Literacy Pathways to Regenerative Civilizations - Künkel, Petra; Ragnarsdottir, Kristin Vala (Springer Nature, 2022)
This open access book brings science and practice together and inspires a global movement towards co-creating regenerative civilizations that work for 100% of humanity and the Earth as a whole. With its conceptual foundation of the concept of transformation literacy it enhances the knowledge and capacity of decision-makers, change agents and institutional actors to steward transformations effectively across institutions, societal sectors and nations. Humanity is at crossroads. Resource depletion and exponential emissions that not only cause climate change, but endanger the health of people and planet, call for a decisive turnaround of human civilization. A new and transformative paradigm is emerging that advocates for regenerative civilizations, in which a narrative of systemic health as much as individual and collective vitality guide the interaction of socio-economic-ecological systems. Truly transformative change must go far beyond technical solutions, and instead envision what can be termed 'a new operating system' that helps humankind to live well within the planetary boundaries and partner with life's evolutionary processes. This requires transformations at three different levels: · Mindsets that reconnect with a worldview in which human agency acknowledges its co-evolutionary pathways with each other and the Earth. · Political, social and economic systems that are regenerative and foster the care-taking for Earth life support systems. · Competencies to design and implement effective large-scale transformative change processes at multiple levels with multiple stakeholders. This book provides key ingredients for enhancing transformation literacy from various perspectives around the globe. It connects the emerging practice of stewarding transformative change across business, government institutions and civil society actors with the most promising scientific models and concepts that underpin human action to shape the future collectively in accordance with planetary needs. ;